Not One of the Family : Foreign Domestic Workers in Canada - Stasiulis, Daiva K.; Bakan, Abigail B. (Abigail Bess), 1954- (Book collections on Project MUSE., 1997)
"In Not One of the Family, workers-turned-activists and experts on foreign domestic workers document how the Canadian system has institutionalized unequal treatment of citizen and non-citizen workers. Since the 1940s rights of citizenship for immigrant domestic workers in Canada have declined, while the number of women recruited from Third World countries to work in Canadian homes has dramatically increased. The analysis is Not One of the Family is both theoretical and practical, framing ideologies of privacy, maternalism, familialism, and rights, as well as examining government policy, labour organizing, and strategies to resist exploitation." "A key resource for all centres for women and immigrant workers, Not One of the Family is also essential reading for civil rights and immigration lawyers, labour groups, and government policy makers."--Jacket.